Exploring graphene oxide intrinsic electroactivity to elucidate the non-covalent interactions with DNA oligonucleotides. Issue 16 (2nd February 2022) - Liang, Yaquan; Ang, Wei Li; Lim, Rachel Rui Xia; Bonanni, Alessandra
Abstract : The intrinsic electroactivity of nano-graphene oxide can be used to elucidate the interactions with DNA oligonucleotides with different sequences. Abstract : We show here how the electrochemical reduction signal of graphene oxide nanocolloids is inhibited upon the formation of non-covalent interactions with single stranded DNA oligonucleotides. The drop in the reduction current intensity is strongly influenced by the nucleobase sequence, and can therefore be directly correlated to the specific DNA homo-oligonucleotide.